2000
DOI: 10.1177/00220345000790041501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in vitro Acidification on Plaque Fluid Composition With and Without a NaF or a Controlled-release Fluoride Rinse

Abstract: Plaque fluid ion concentration changes, especially fluoride, in response to the pH decrease associated with a cariogenic episode are important components of the caries process. A "controlled-release" (CR) fluoride rinse, based on the controlled release of fluoride in the presence of calcium, has been shown to form large fluoride reservoirs in resting plaque. In this study, the in vitro acid-induced release of fluoride, and other ions, was examined in 48-hour-fasted plaque fluid from subjects (n = 11) who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 44 publications
4
37
0
2
Order By: Relevance
“…0.05 was used in all statistical tests. As in similar studies, a very large range of fluoride values was found, especially in the fluoride plaque data after the experimental rinse, which, as in previous studies, was usually due to one or two outliers in the data set [Duckworth, 1994;Vogel et al, 1997Vogel et al, , 2000Vogel et al, , 2001. Three 'extreme' outliers from one individual were removed from the salivary data set using the criteria previously described [Vogel et al, 1997].…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…0.05 was used in all statistical tests. As in similar studies, a very large range of fluoride values was found, especially in the fluoride plaque data after the experimental rinse, which, as in previous studies, was usually due to one or two outliers in the data set [Duckworth, 1994;Vogel et al, 1997Vogel et al, , 2000Vogel et al, , 2001. Three 'extreme' outliers from one individual were removed from the salivary data set using the criteria previously described [Vogel et al, 1997].…”
Section: Methodsmentioning
confidence: 90%
“…The controlled-release experimental fluoride rinse, which uses the controlled release of fluoride from the hydrolysis of Na 2 SiF 6 in the presence of CaCl 2 to enhance the deposition of fluoride in oral tissue [Vogel et al, , 2001Chow et al, 2000], was chosen for these experiments for the following reasons: (1) in agreement with the studies described in the introduction, a preliminary experiment using similar experimental conditions found no effect on lactic acid production with an NaF rinse [Vogel, unpubl. data], and (2) compared with an NaF rinse, the experimental rinse produced a much higher concentration of plaque and plaque fluid fluoride and a greater release of fluoride when plaque was acidified [Vogel et al, 1992[Vogel et al, , 2001, suggesting that a positive effect might be observed.…”
Section: Choice Of Experimental Conditions and Rinse Formulationmentioning
confidence: 99%
“…Different chemical properties and surface topographies of the various materials may play a role in biofilm formation and influence the differences in composition and general properties from one to another [24][25][26] . Several studies have found that the fluoride added to materials can alter wettability and plaque formation, as well as the adherence of Streptococcus mutans [27][28][29][30] . However, other authors contend that the presence of fluoride on dental materials does not modify the materials' basic characteristics 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…The second spectrum, from the bottom, demonstrates XRD patterns for precipitation of CaF 2 when polymer K-702 with 5 mg/L is used, indicating the presence of constituents A, B, and C. According to ICDD NO. 441938, 411907, and 441588, the A, B, and C, were assigned to C 6 …”
Section: X-rays Diffraction (Xrd)mentioning
confidence: 99%
“…These studies reveal that these inhibitors, when present at low concentration, markedly influence the crystallization kinetics. In oral care applications, calcium fluoride plays a key role in the topical application of fluoride solution to tooth enamel, the hydroxyapaptie, (HAP), Ca 5 (PO 4 ) 3 OH, (the main inorganic component of tooth enamel) is converted to fluoroapaptie, (FAP), Ca 5 (PO 4 ) 3 OF, on the enamel surface resulting in a much more carrier resistant phase [6]. The high concentration of Fluoride ion, CaF 2 forms at the tooth surface in addition to fluoroapitate (FAP).…”
Section: Introductionmentioning
confidence: 99%